ANALYSIS OF CHANGES IN TEMPERATURE, HUMIDITY, AND RAINFALL PARAMETERS IN RELATION TO TRENDS IN DENGUE FEVER (DBD) CASES IN TANGERANG REGENCY - Muhamad Rayhan Dwi; Yayat Ruhiat; Devi Ayu Nur'aini (Pascal: Journal of Physics and Science Learning, 2026)
The high epidemiological burden of dengue fever in Tangerang Regency, a densely populated lowland area in Banten, provided the background for this study. Its primary objective was to describe climate fluctuations and analyze the partial relationships between temperature, humidity, and rainfall and dengue fever cases using secondary data from 2020 to 2024. The method combines physical descriptive analysis and Spearman’s rank correlation test. Visualization results show an optimal physical equilibrium in 2024 that triggered the highest spike in cases (5,088). Temperature showed a weak negative correlation (–0.300), humidity a strong positive correlation (0.600), and rainfall a very strong positive correlation (0.700), although sample limitations resulted in formal non-significance (p > 0.05). Physically, rainfall provides breeding sites for larvae, while humidity extends the lifespan of the vector; however, extreme rainfall triggers a mechanical flushing effect. These findings emphasize the need for public health agencies to incorporate rainfall and humidity indicators into early warning systems to strengthen preventive mitigation measures ahead of the peak of the transmission season.